True New Agenda for South East Europe and EU - Teqja, Eva (Richtmann Publishing, 2012)
The purpose of this paper is to explain, in a clear and concise way, how the EUâ€™s enlargement policy is affecting westernBalkans countries. It aims to give an overview of how the EU strategy has grown since this idea is created. Where it stands today afterhaving undergone its most important round of enlargement and what the perspective of accepting new members in the future is. Theproposed paper examines how is proceeding EU with its next enlargement round in the conditions of so called â€œenlargement fatigueâ€ thathas gripped the European Union, with the global financial and economic crisis drawing much attention away from the Balkans accessionissue. And in the other hand, as a result of this if inhabitants of the Western Balkans are becoming increasingly aware that enlargementis no longer fashionable in the EU. The paper discusses about the fact that EU member states should strongly reaffirm their Thessalonikicommitment, and so even further by giving their support to EU accession proposals for the western Balkans in the European Council.Furthermore it addresses the problem of the completion of the process in the region, the commitment of the EU in the front of theBalkans European future, the major challenges that have to affront both of them, the problems in the European home, and the duties ofWestern Balkans countries.Despite a number of unresolved issues in the region, one can see a new spirit of rapprochement and genuinecooperation in the Western Balkans enlargement is a strategic policy decision of the European Union. Elaborating the advancementmeasures to sustain the current rapprochement policy over the period ahead is a priority. The moment must be seized and the trendmust be translated into an irreversible process. This is where South-East Europe and the European Union could find a true new agenda.